High Fuel Price and Performance of Organisations: A Case Study of Nile Plastics Company Limited in Uganda - Ambrose Okello (Uganda Christian University, 2025)
This study explores the impact of escalating fuel prices on organizational performance, using Nile Plastics Company Limited in Uganda as a case study. The research examines how high fuel costs influence key performance indicators, including operational expenses, sales volume, profitability, and market share. A descriptive, cross‑sectional design was employed, with quantitative data collected via structured questionnaires distributed to staff across departments within the company. Findings indicate that high fuel prices driven by geopolitical tensions, fluctuations in exchange rates and elevated taxation substantially increase operational costs, disrupt supply chains, and erode profitability and sales performance. Mitigation strategies such as efficient route planning, bulk purchasing, and cost-cutting measures are implemented but are largely reactive and insufficient. The study recommends more proactive measures, including government tax incentives, investment in alternative energy sources, and enhanced contingency planning by organizations. These insights are significant for policymakers and businesses in the oil, gas, and manufacturing sectors aiming to strengthen resilience against fuel price volatility. Keywords: fuel prices, organizational performance, operational costs, supply chain, mitigation strategies